2011
DOI: 10.1620/tjem.224.189
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Blood Interferon-Gamma Release Assay for Diagnosis of Tuberculous Lymphadenitis

Abstract: Tuberculosis remains a major problem for much of the world. Tuberculous lymphadenitis is the most common type of extrapulmonary tuberculosis, although a difficult invasive procedure is required for its diagnosis. We evaluated the usefulness of the whole-blood interferon-gamma release assay (IGRA) for diagnosis of tuberculous lymphadenitis. From January 2008 to October 2010, 108 patients underwent lymph node biopsy and the IGRA concurrently in Wonju Christian Hospital, Yonsei University Wonju College of Medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…1) (Cho et al, 2011; Jia et al, 2016; Jia et al, 2014; Kim, Ko & Kim, 2013; Kim, Kim & Woo, 2016; Kim et al, 2011; Liao et al, 2009; Lu et al, 2016; Shin et al, 2015; Song et al, 2009). The basic characteristics of each study are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1) (Cho et al, 2011; Jia et al, 2016; Jia et al, 2014; Kim, Ko & Kim, 2013; Kim, Kim & Woo, 2016; Kim et al, 2011; Liao et al, 2009; Lu et al, 2016; Shin et al, 2015; Song et al, 2009). The basic characteristics of each study are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, the IGRA studies focused on the detection of active pulmonary TB, but there are limited data of diagnostic performance focused on extrapulmonary TB, such as tuberculous lymphadenitis (23)(24)(25)(26). Although there was a very small number of patients (total 68 patients with TB lymphadenitis), the IGRA showed a sensitivity of approximately 90% in TB lymphadenitis based on these studies.…”
Section: Discussionmentioning
confidence: 98%
“…The overall annual incidence ranged from 0.0% to 1.05% of all TB infections. Some investigators have reported that IGRAs are useful for diagnosing E-TB, which includes TB lymphadenitis most commonly, and pleural, skeletal, central nervous system, and abdominal TB less commonly [7-9,23]. The reported sensitivities and specificities of IGRAs for the diagnosis of E-TB are 69% to 94% and 82% to 88%, collectively, and vary among disease sites [7-9].…”
Section: Discussionmentioning
confidence: 99%
“…The reported sensitivities and specificities of IGRAs for the diagnosis of E-TB are 69% to 94% and 82% to 88%, collectively, and vary among disease sites [7-9]. In patients with suspected TB lymphadenitis, blood IGRA may be useful adjunct assay to diagnose or exclude E-TB [8,23], but blood IGRA alone is not useful for diagnosis of TB of the spine or central nervous system [8,24]. Previous studies included no or few, if any, hepatic or splenic TB patients and no other studies have evaluated the usefulness of the QFT-GIT for diagnosing hepatic or splenic TB in hematologic patients.…”
Section: Discussionmentioning
confidence: 99%